Estudo das propriedades ópticas do nanocompósito de dissulfeto de molibdênio e nanofibrilas de celulose - Camilo, Antonio Carlos Eleutério (2019)
Studies on nanocomposite dicalcogenated transition metals (TMDs) with cellulose nanofibrils (CNFs), called TMD-CNFs, are still scarce in the literature. Among the TMDs, molybdenum disulphide (MoS2) has great application versatility. MoS2 nanocomposite was obtained with CNFs (MoS2-CNFs) and their optical properties were studied by spectral and microscopic techniques. MoS2 monolayers were obtained with CNFs by sonication in aqueous medium and centrifugation. It was demonstrated by the Dynamic Light Scattering (DLS) and Zeta Potential (ZP) analyzes that the sonication process is efficient to obtain a MoS2 monolayer (m-MoS2) and cellulose can be used as a stabilizer of the monolayers, reaching average size of 270 nm for MoS2 and 700 nm for MoS2-CNFs in colloidal suspension, with -37.92 mV of ZP in 20% v/v of added CNFs. It has been found that the CNFs agglutinate on the surface of the MoS2 flakes by Van der Waals forces. Through AFM analysis, the average thickness of 5 nm for the MoS2 flakes was found. It has been shown that the MoS2 presents 2H geometry because it presents a second harmonic emission (SH) null in paired monolayers. UV/VIS spectroscopy analyzes shows that the addition of cellulose caused significant improvements in the absorption bands of the MoS2 monolayers (m-MoS2), similar as a single MoS2 monolayer. Morphological analyzes of the MoS2-CNFs composite indicate that this occurs because the addition of the CNFs reduces the disorientation of the MoS2 flakes. Strong fluorescence (FL) and second harmonic generation (SHG) were found in m-MoS2 through Confocal Microscopy (CM) analyzes. The presence of few m-MoS2 on the surface of the MoS2 flakes justifies the high fluorescence emission of the nanocomposite. Results indicate that addition of CNFs results in loss of fluorescence. However, the amount of SH regions increases as a function of fluorescence.